Analysis of Organizational Culture and Employee Loyalty at Bank Sumedang - Sukmayadi, Sukmayadi; Ramadhyanti, Destiany (SINTESA, 2023)
The background of this study is that there are indications of an organization at Sumedang Bank that has been running quite well but needs to be optimized. This study aims to apply organizational culture knowledge and determine the application of organizational culture and determine employee loyalty at Sumedang Bank. This research uses qualitative research methods with data collection techniques, namely interview observation and documentation. The informants in this study were determined using the purposive sampling method, namely a total of 6 people. The final results of this study concluded that the culture organizational owned by Bank Sumedang had been going well but was still not optimal in the way it behaved, dress, and so on. While employees at Bank Sumedang have been running well but not optimally. This can be seen from several things, namely there are several bank employees because they are late for work from the specified hours. Therefore, the results of this study can be used as references and recommendations to support the smooth running of Organizational Cultute and Employee Loyalty at Bank Sumedang